2007
DOI: 10.1097/mlg.0b013e318068b566
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Fat at Autopsy

Abstract: Increase in tongue weight and percentage of fat, and therefore tongue volume, may explain why patients with weight gain have higher rates of SDB. Tongue weight, fat, and volume may also correlate with and explain Mallampati grades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 4 publications
7
93
2
8
Order By: Relevance
“…Nashi et al studied the tongues from 121 consecutive medical examiner cases and observed a high fat content in this organ, mainly in the posterior third. The Nashi group also verified that the weight, volume and fat content of the tongue were associated with a higher BMI, suggesting an association between obesity and a modified Mallampati grade of 3 or 4 27 . Modern image acquisition studies have shown an association between anatomical characteristics, such as large tongues and narrowed upper airways, and OSAS 28 .…”
Section: Discussionmentioning
confidence: 97%
“…Nashi et al studied the tongues from 121 consecutive medical examiner cases and observed a high fat content in this organ, mainly in the posterior third. The Nashi group also verified that the weight, volume and fat content of the tongue were associated with a higher BMI, suggesting an association between obesity and a modified Mallampati grade of 3 or 4 27 . Modern image acquisition studies have shown an association between anatomical characteristics, such as large tongues and narrowed upper airways, and OSAS 28 .…”
Section: Discussionmentioning
confidence: 97%
“…We anticipated that the volume of the parapharyngeal fat pads would be greater in NZO mice than in leaner NZW mice, as was previously shown in obese human patients with OSA (6,7,25). It has also been shown that obese humans have fat infiltration of their tongue, which increases with the degree of obesity (26). This likely contributes to enlargement of the tongue, and we have shown that increased tongue size in patients with OSA is a risk factor for OSA (6,27).…”
mentioning
confidence: 77%
“…The tongue is composed of muscular and fatty tissue. An autopsy study (26) demonstrated that the human tongue has a remarkably high percentage of fat and that increasing tongue weight and percentage of tongue fat are associated with increasing obesity. Apnea was not examined in that study.…”
Section: Size Of Upper Airway Soft Tissue Structures In the Nzo Mousementioning
confidence: 99%
“…2 Obesity may modify the upper airway through the enlargement of the upper airway soft tissues, especially the tongue. 3,4 Several other factors, including neuromuscular modulation, control of breathing, and arousal threshold, may contribute to OSA severity as expressed by AHI. 5,6 All these factors may interact differently according to sex, age, and ethnicity.…”
mentioning
confidence: 99%